Familial dominant epilepsy and mild pachygyria associated with a constitutional LIS1 mutation. Issue 12 (25th August 2018) - De Vita, Dalila; Mei, Davide; Rutigliano, Domenico; Bartalucci, Niccolò; Cinnante, Claudia Maria; Parrini, Elena; Dilena, Robertino; Guerrini, Renzo
Abstract : We describe a mother and son with focal epilepsy, mild cognitive impairment, and pachygyria, which was parieto‐occipital in the mother and with remarkable posterior greater than anterior severity in the son. Overall clinical manifestations, although overlapping in type, were likewise slightly more severe in the son. Using targeted resequencing through a gene panel for malformations of cortical development, we identified the c.655 T > A [p.(Trp219Arg)] novel missense variant in the LIS1 gene, segregating in the proband and in his mother. Western Blot analysis, qPCR gene expression and RT‐PCR disclosed no significant differences between proband, his parents, and controls. Epilepsy and mild cognitive impairment can be the only clinical presentation of constitutional LIS1 mutations, which can therefore be inherited if the associated phenotype implies limited or no reproductive disadvantage. Parents of patients harboring LIS1 mutations should be assessed for their mutation carrier status.